The impact of the educational environment on student engagement and academic performance in health professions education - Salah Eldin Kassab; Ramya Rathan; David C. M. Taylor; Hossam Hamdy (BMC Medical Education)
Abstract Background This research explores the relationships between the educational environment, student engagement, and academic achievement in Health Professions Education (HPE) , specifically examining the mediating role of engagement. Methods The study used cross-sectional design, and data were collected from 554 HPE students via self-report questionnaires. The Dundee Ready Education Environment Measure (DREEM) assessed the educational environment while the University Student Engagement Inventory measured learning engagement across the behavioral, emotional, and cognitive dimensions. Academic achievement was measured using cumulative GPA. Relationships between study variables were analyzed using path analysis. Results Path analysis demonstrated that four educational environment subscales directly affected emotional engagement (48% variance explained). Students’ perception of learning and academic self-perceptions influenced behavioral engagement (28% variance explained), while cognitive engagement was influenced by academic self-perceptions (39% variance explained). GPA was positively influenced by behavioral and cognitive engagement but negatively by emotional engagement. Cognitive and behavioral engagement mediated the relationship between students’ academic self-perceptions and academic achievement. Conclusions Students’ perceptions of the educational environment significantly influenced emotional engagement, followed by cognitive and behavioral engagement. Cognitive and behavioral engagement directly affected academic achievement and mediated the relationship between the educational environment and academic achievement.